Coupling the post-extraction process to remove residual lignin and alter the recalcitrant structures for improving the enzymatic digestibility of acid-pretreated bamboo residues. (August 2019) - Huang, Caoxing; Lin, Wenqian; Lai, Chenhuan; Li, Xin; Jin, Yongcan; Yong, Qiang
Highlights: Post-extraction removed the lignin and disrupted inhibitory properties. Urea-extraction can remove 30% of lignin for enhancing the enzymatic hydrolysis. Post-extraction improved enzymatic digestibility of acid-pretreated bamboo. Physicochemical features showed correlations with enzymatic digestibility. Abstract: In this work, a mild and facile post-extraction using different reagents was evaluated to overcome these recalcitrance for improving the enzymatic digestibility of acid-pretreated bamboo residues by removing the lignin and disrupting its inhibitory properties. Results showed that the enzymatic digestibility of acid-pretreated bamboo residues can be improved from 15.4% to 61.4%, 59.7%, and 42.8% by room temperature post-extraction with phosphoric acid, urea, and ethanol, respectively. Several compelling correlations (R 2  > 0.5) were observable between enzymatic digestibility and structural changes, including delignification, reducing of substrate hydrophobicity, altering cellulose crystallinity, and elevations to the residual lignin syringyl-to-guaiacyl (S/G) ratio and functional groups. The results serve as a demonstration of the downstream value that can be gained when coupling a post-extraction process with acid pretreatment of bamboo residues, resulting in greater fermentable sugar production.